Comparative Analysis of Dimension and Cost Planning of Designed Upper Structure Elements With SRPMB, SRPMM, and SRPMK Structural Systems - Totok Andi Prasetyo; Fauzan Nabil (International Journal Labs, 2025)
In general, industrial buildings are built using steel material as the main structure. The most basic structural elements used in industrial buildings consist of columns and rafters as the main frame. The combination of columns and rafters in a portal frame system forms a strong, efficient, and flexible structure for various industrial building needs. In the context of building planning in Indonesia, there are several systems that can be applied, namely the Ordinary Moment Resisting Framing Systems (OMRFS), Intermediate Moment Resisting Frame Systems (IMRFS), and Special Moment Resisting Framing Systems (SMRFS). Each of these systems has different characteristics, so the selection must be adjusted based on the seismic design category. This final project compares the dimension planning and cost of structural elements in warehouse buildings designed with three different structural systems, namely OMRFS, IMRFS and SMRFS. The analysis was carried out using ETABS v.18 software and manual calculations in accordance with SNI 1726: 2020, SNI 1729: 2020, and SNI 2860: 2020. Based on the results of the ETABS v.18 software analysis and manual calculations, the overall weight volume of the structural element dimensions of each structural system is OMRFS of 227.67 tons, IMRFS of 241.31 tons and SMRFS of 350.73 tons. For the value of the budget plan cost on OMRFS obtained at Rp. 8,986,525,987, for IMRFS obtained at Rp. 9,460,556,532, and SMRFS obtained at Rp 13,253,952,870.